Therapeutic dilemma : alcohol withdrawal syndrome and concurrent hepatic encephalopathy. A case report (2021)
Alcohol use disorder is one of the main causes of morbidity and mortality in the world. Alcoholic liver disease is a common complication of this disorder, and hepatic encephalopathy is a serious complication of alcoholic cirrhosis. Precipitating factors m